Relationship of Intellectual Capital, Work Environment and Human Resources Engagement with Community Health Center Performance Using the SEM-PLS Approach - Ahmad Faridi; Masyhdzulhak Djamil; Ahmad Badawi Saluy; Mafiztun Nurhayati (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
In this study, the use of intellectual capital, work environment, and human resources engagement variables was associated with the performance of the community health center (in Indonesia: puskesmas). The sub-district health centers in Kebayoran Lama District in South Jakarta were the subject of this study, involving about 34 health workers as research samples. All health workers in the population were used as a sample because the saturation sampling technique was used when there were less than 100 samples. The Likert scale was used to measure the variables involved in this lesson.This study used a questionnaire, quantitative methodology, and structural equation models (SEM) with the partial least squares (PLS) technique for analysis. The SMARTPLS 3.2.9 software was used to process the data for this investigation. The results of this study indicated that the performance of the community health center can be maximized by optimizing intellectual capital and the work environment by taking into account the involvement of human resources for health workers associated with improving the performance of the Sub-district Health Center in the working area of the Kebayoran Lama District Health Center.